Pengaruh Brand Image dan Sosial Media Marketing Terhadap Keputusan Pembelian Dengan Minat Belo Sebagai Variabel Intervening: Studi Kasus pada Pembeli Geprek Bp7 di Kota Tebing Tinggi - Batubara, Rizki Wulanita; Kisfa, Ajreni (Digital Business Progress, 2024)
This research aims to determine the influence of brand image and social media marketing on purchasing decisions with purchase interest as an intervening variable (Case Study of Geprek Bp7 in Tebing Tinggi City). This type of research is quantitative descriptive research. The research population includes Geprek BP7 customers in Tebing Tinggi City. The research sample consisted of 66 respondents. The sampling method uses the probability sampling method. Research data uses primary data sources. Data was obtained from the results of distributing questionnaires to respondents. The data analysis method uses the path analysis method. The results of the analysis show that brand image influences purchasing interest in geprek bp7, Tebing Tinggi City, social media marketing influences purchasing interest, brand image influences purchasing decisions, social media marketing influences purchasing decisions, purchasing interest influences purchasing decisions, purchasing interest can mediating the relationship between brand image and purchasing decisions and purchasing interest can mediate the relationship between social media marketing and purchasing decisions at Geprek BP7, Tebing Tinggi City.